Irrigation technology for smallholder farmers: a strategy for achieving household food security in Lower Gweru, Zimbabwe - Dube, Kaitano; Sigauke, E. (My University, 2015)
The problem of food insecurity in developing countries is an enormous challenge. In rural communities, it is a perennial problem that requires undivided attention to ensure household food security. This paper seeks to define the role of rural participation in providing household and community food security with a particular focus on Lower Gweru irrigation project in Zimbabwe. The research comes in light of increased food deficit in Zimbabwe that has been compounded by failed politics, climate change and weather extreme events. Data was gathered using self-administered questionnaires, direct observation and literature review. Data was analysed using the Microsoft Excel 365 ToolPak and Health24 Web Calculator. This paper highlights the importance of rural irrigation schemes in addressing community and household food security and ensuring health nutrition uptake by irrigators and surrounding communities. Rural irrigation systems enable farmers to become net food sellers allowing them to benefit from food price volatility. It also highlights the resultant development and makes recommendations for future irrigation developments
Keywords: Food security; Irrigation; Climate change; Nutrition; Zimbabwe; Rural irrigation schemes